Enterprising Worlds A Geographic Perspective on Economics, Environments & Ethics - Gatrell, Jay D.; Reid, Neil.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Enterprising World represents the culmination of several years of work by geographers, planners, and economists. The chapters included in this volume represent the collective efforts of the International Geographical Union$1 (Bs Commission on the Dynamics of Economic Spaces. This collection is the result of the 2005 annual meeting in Toledo, Ohio (USA). The chapters have been selected based on their contribution to the broader community of economic geographers and policymakers and to demonstrate the inherent interconnectedness of these themes (and at times the conceptual tension that exists between ethics, economics, and the environment) insofar as these important issues shape the contours and cleavages of contemporary regional development. In particular, the chapters represent the diversity of perspectives on these issues. The authors provide insight into the workings of a variety of communities, regions, and nations as they seek to balance economic growth with the growing necessity to simultaneously promote ethical and sustainable regional development. As such, this book is truly international in both scale and scope and provides the reader with a survey of emerging and established concepts, theories, and conflicts in economic geography.s
Economics, Environments & Ethics -- Industrial and Technology Clusters: An Everyday Topic of Popular Conversation -- Which Mode of (CLUSTER) Promotion for which aspect of Entrepreneurship? A differentiating view on institutional support of automotive clusters -- The Dynamics of FDI of the TFT-LCD Cluster: A Study of Japanese Firms in Taiwan -- Collaborating to Compete: The Case of Northwest Ohio$1 (Bs Greenhouse Industry -- Specialized Agriculture: Local Markets & Global Competitors in Ohio$1 (Bs Greenhouse Industry -- High Technology and Urban Development in Bangalore, India -- An Evolutional Model of U.S. Manufacturing and Services Industries -- Clusters and Local Economic Growth: Unpacking the Cluster Model -- Towards Reconceptualising Enterprise, Entrepreneurship and Entrepreneurial Processes for Sustainable Futures: Contributions from Economic Geography -- Attitudes, Behaviours and Outcomes of Different Types of Entrepreneurs: Toward a Better Understanding of the Multiple Entrepreneurship Phenomenon -- The Business and Sustainability of Water Supply in Singapore: The Case of Hyflux -- Entrepreneurship: New Means of Support for Community Colleges -- Globalization, Social Protest and the Militarized Landscape of Okinawa -- Paternalism and Struggle at Weirton Steel Corporation -- Ethics in Economic Geography -- Whose Development? The Tribal Involuntary Dislocation in the Sardar Sarovar -- Geographies of Informalization: Conceptual Dilemmas over Social Standards and Informalization of Labor -- Building or Repairing Institutions: Microcredits in Argentina -- Bread or Circus? The Economics of Mega-Sporting Events -- Social Entrepreneurship and Regional Economic Development: A Conceptual Framework.s
Keywords: Geography; Economic geography; Regional planning; Urban planning; Economic growth; Human geography; Geography; Economic Geography; Economic Growth; Human Geography; Landscape/Regional and Urban Planning; Electronic books